2018
DOI: 10.1182/blood-2018-99-111370
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib + Obinutuzumab Versus Chlorambucil + Obinutuzumab As First-Line Treatment in Patients with Chronic Lymphocytic Leukemia or Small Lymphocytic Lymphoma (CLL/SLL): Results from Phase 3 iLLUMINATE

Abstract: Background : Ibrutinib (ibr), a first-in-class, once-daily inhibitor of Bruton's tyrosine kinase, is approved in the US and EU for patients (pts) with CLL and allows for treatment without chemotherapy. Standard of care for first-line CLL in older pts or those with comorbidities includes single-agent ibr and chemoimmunotherapy (CIT) with chlorambucil (clb) plus anti-CD20 therapy. As the addition of obinutuzumab (G) to clb provides superior efficacy over clb alone or rituximab-G, we investigated the potential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In the E1912 trial of young (≤ 70 years of age), fit patients with TN CLL, ibrutinib combined with rituximab led to superior PFS and OS compared with FCR [20], whereas in the ALLIANCE A014202 trial of fit, older patients (≥ 65 years of age), first-line treatment with single-agent ibrutinib or ibrutinib + rituximab significantly prolonged PFS compared with BR [21]. Further, in the iLLUMINATE study of patients with CLL and ≥ 65 years of age (or younger but with comorbidities), a chemotherapy-free regimen of ibrutinib + obinutuzumab improved PFS, response rates, and depth of remission compared with chlorambucil + obinutuzumab chemoimmunotherapy, irrespective of the presence of high-risk genomic features [22]. These RCT findings are likely to be practice changing in the TN setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the E1912 trial of young (≤ 70 years of age), fit patients with TN CLL, ibrutinib combined with rituximab led to superior PFS and OS compared with FCR [20], whereas in the ALLIANCE A014202 trial of fit, older patients (≥ 65 years of age), first-line treatment with single-agent ibrutinib or ibrutinib + rituximab significantly prolonged PFS compared with BR [21]. Further, in the iLLUMINATE study of patients with CLL and ≥ 65 years of age (or younger but with comorbidities), a chemotherapy-free regimen of ibrutinib + obinutuzumab improved PFS, response rates, and depth of remission compared with chlorambucil + obinutuzumab chemoimmunotherapy, irrespective of the presence of high-risk genomic features [22]. These RCT findings are likely to be practice changing in the TN setting.…”
Section: Discussionmentioning
confidence: 99%
“…In randomized registration trials of patients with CLL, ibrutinib significantly improved progression-free survival (PFS) and overall survival (OS) versus chlorambucil in TN patients (RESONATE-2™; NCT01722487) [13] and versus ofatumumab in R/R patients (RESONATE™; NCT01578707) [14]. Additional head-to-head clinical trial comparisons of ibrutinib-based regimens versus other widely used treatments (including current standard-of-care chemoimmunotherapy regimens and other novel regimens incorporated into CLL guidelines [1517]) are ongoing [18, 19], and recent results from multiple phase 3 trials have been positive [data available as abstracts] [2022].…”
Section: Introductionmentioning
confidence: 99%
“…There were no difference between arms; the mean score for Activities of Daily Living (ADL) was 13.7 (possible range 0-14; higher is better), mean score for Instrumental ADL was 79.7 (possible range 0-100; higher is better), 9.7% had ≥1 falls in the last 6 months, 5.4% screened positive for cognitive impairment (using the Blessed Orientation Memory Concentration Test), and 23.9% had N5% weight loss in the last 6 months. In another phase 3 trial, iLLUMINATE, presented by Moreno et al, the combination of ibrutinibobinutuzumab was superior to chlorambucil-obinutuzumab in patients aged ≥65 years, or b 65 years with pre-existing conditions (median age 71 years) [11]. PFS with ibrutinibobinutuzumab was not reached compared to 19 months with chlorambucil-obinutuzumab [HR 0.23, p < .0001), with similar toxicity profiles.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 98%
“…In contrast, the rate of grade 3, 4, or 5 nonhematological AEs was lower in the BR arm (63%) than with the ibrutinib-containing regimens (74% for IR or ibrutinib alone). An industry-sponsored study, the phase 3 iLLUMINATE trial, indicated that the combination of ibrutinib and obinutuzumab provided a 77% reduction in the risk of progression or death compared to chlorambucil and obinutuzumab 10,11 (Table 1).…”
Section: Ibrutinib Vs Chemo-immunotherapy As First-line Therapymentioning
confidence: 99%